Pendidikan Vokasi dan Pengangguran Usia Muda - Rahmawati Koto Rahmawati Koto; Sri Maryati Sri Maryati (Universitas Negeri Padang, 2025)
Vocational education is a form of education that emphasizes the mastery of practical skills and technical knowledge required for employment in specific industries or sectors. This study aims to analyze the impact of vocational education on youth unemployment in Indonesia. A quantitative approach was employed using logistic regression analysis with primary data. The sampling technique used was stratified random sampling. The variables included the type of educational institution, work experience, ownership of a pre-employment card, gender, and region. The results showed that vocational education, pre-employment cards, educational institutions, gender, and region significantly influence youth unemployment, while work experience does not. Vocational education plays a crucial role in addressing youth unemployment by providing skills and knowledge relevant to labor market needs.